A bibliometric review on safety risk assessment of construction based on CiteSpace software and WoS database - Junjia, Yin; Alias, Aidi Hizami; Haron, Nuzul Azam; Abu Bakar, Nabilah (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
As urbanization continues to grow around the world, the risks associated with construction are increasing. Scientific and practical risk assessments help reduce safety risks and achieve healthy, long-term growth, so there has been much research in this field. Through a review of the literature, this study aims to reveal the state and trends of research in the field of safety risk assessment. We searched 473 articles on construction risk assessment from the Web of Science (WoS) in the last decade, bibliometrically analyzed them, and then uncovered their significance using CiteSpace software (6.1. R6 (64-bit) Basic). The primary topics of conversation are countries, institutions, authors, and keywords, followed by references. According to the co-authorship analysis, the current research in this field is mainly from China, the USA, and Australia. Most influential authors currently have teaching or research positions at educational institutions; the most notable of which include Huazhong University of Science and Technology, Hong Kong Polytechnic University, and Tsinghua University. They form a relatively close network of institutional cooperation. Based on the results of the co-term analysis, this study found that the current research hotspots are mainly focusing on “multi-objective optimization”, “risk management”, “mechanical characterization”, “mental fatigue”, “accident prevention”, and many others. Data-driven, AI-assisted, and multi-stakeholder participation are the future trends in this field.